Một vài thuật toán cài đặt các phép toán của đại số quan hệ trong mô hình dữ liệu dạng khối - Huy, Nguyễn Xuân; Thắng, Trịnh Đình (Journal of Computer Science and Cybernetics, 2016)
This paper presents some fundamental results about the block form - relational algebra together with algorithms realizing some block form - relational operators. Also, the estimation complexity of these algorithms are claimed and proved here.